Analysis of the Effectiveness of Bamboozle Interactive Media on Elementary School Students’ Mathematics Learning - Nanda Adelia; Berta Apriza (International Journal of Elementary Education, 2025)
The development of information and communication technology has encouraged the integration of digital media into mathematics learning however, the effectiveness of game based media still requires comprehensive examination. This study aims to analyze and synthesize the effectiveness of Bamboozle interactive media in elementary school mathematics learning. This research employed a Systematic Literature Review (SLR) approach, with relevant scientific articles serving as the research subjects. Data were collected through a systematic search of the Google Scholar database using the keywords “media,” “Bamboozle,” “mathematics,” and “elementary school” within the 2021–2025 publication range. Article selection based on inclusion and exclusion criteria resulted in ten articles that were analyzed descriptively and qualitatively through categorization and synthesis of findings. The results indicate that Bamboozle effectively enhances students’ motivation, interest, and engagement, while also strengthening conceptual understanding and mathematics learning outcomes. The conclusion of this study explicitly confirms that Bamboozle is an effective and relevant instructional medium for improving the quality of elementary mathematics learning. The implication is that teachers and educational institutions should systematically integrate game based digital media into instructional strategies to foster innovative, participatory, and technology-oriented learning environments.